1988
DOI: 10.1111/j.1600-0722.1988.tb01576.x
|View full text |Cite
|
Sign up to set email alerts
|

Buffering effect of antacids in the mouth ‐ a new treatment of dental erosion?

Abstract: Metirman JH, Kuittinen T, Kangas M, Tuisku T: Buffering effect of antacids in the mouth -a new treatment of dental erosioti? ScandJ Dent Res 1988: 96: 412 7.Abstract -Antacids are drugs of choice in the treatmeiU of reflux esophagitis and peptic ulcer disease, where acid regurgitation may cause dental erosion. Since there are no specific preventive measures or effective treatment for erosions, the present study was made to asse.ss whetlier the keeping of antacids in the mouth before swallowing would be benefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 7 publications
(3 reference statements)
2
12
0
Order By: Relevance
“…Volunteers used a series of two min oral rinses after each one min HCl rinse (to mimic the pH of acid reflux) and the acid: base balance in the mouth was followed for 30 min. There was no mention of irritation or other effects of any of the solutions, but overall the results with Al(OH) 3 were consistent with those of Meurman et al (1988) who found chewing an Al(OH) 3 tablet was an effective means to combat dental softening and erosion due to chronic acid regurgitation.…”
Section: Digestive Tractsupporting
confidence: 80%
“…Volunteers used a series of two min oral rinses after each one min HCl rinse (to mimic the pH of acid reflux) and the acid: base balance in the mouth was followed for 30 min. There was no mention of irritation or other effects of any of the solutions, but overall the results with Al(OH) 3 were consistent with those of Meurman et al (1988) who found chewing an Al(OH) 3 tablet was an effective means to combat dental softening and erosion due to chronic acid regurgitation.…”
Section: Digestive Tractsupporting
confidence: 80%
“…These have a more limited clinical effect in dental erosion [129136], even if their positive effect in the prevention of dental caries is well established. The use of neutralizing products such as antacid drugs has been shown to increase intraoral pH after an acidic challenge [137, 138], while rinsing with bicarbonate decreased tooth surface loss after artificially induced erosion, it did not alter surface microhardness [139]. A large variety of dental care products for prevention of dental erosion is on the market but there is no formula or product available today that provides adequate protection against erosion [140].…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…3,4 Such measures include the use of antacids, 5 fluorides 6 and oral hygiene practices. Even though fluoride has been successfully used to inhibit dental caries, its availability through dietary fluoride supplementation programmes or through regular use of fluoridated dentifrices does not appear to result in teeth being more resistant to erosion.…”
mentioning
confidence: 99%